The roles of p27(Kip1) and DNA damage signalling in the chemotherapy-induced delayed cell cycle checkpoint - Liontos, Michalis; Velimezi, Georgia; Pateras, Ioannis S; Angelopoulou, Roxani; Papavassiliou, Athanasios G; Bartek, Jiri; Gorgoulis, Vassilis G (Journal of cellular and molecular medicine, 2010)
DNA lesions trigger the DNA damage response (DDR) machinery, which protects genomic integrity and sustains cellular survival. Increasing data underline the significance of the integrity of the DDR pathway in chemotherapy response. According to a recent work, persistent exposure of A549 lung carcinoma cells to doxorubicin induces an initial DDR-dependent checkpoint response, followed by a later DDR-independent, but p27(Kip1)-dependent one. Prompted by the above report and to better understand the involvement of the DDR signaling after chemotherapeutic stress, we examined the potential role of the canonical DDR pathway in A549 cells treated with doxorubicin. Exposure of A549 cells, prior to doxorubicin treatment, to ATM, ATR and DNA-PKcs inhibitors either alone or in various combinations, revealed that the earlier documented two-step response was DDR-dependent in both steps. Notably, inhibition of both ATM and ATR or selective inhibition of ATM or DNA-PKcs resulted in cell-cycle re-entry despite the increased levels of p27(Kip1) at all time points analyzed. We further investigated the regulation of p27(Kip1) protein levels in the particular setting. Our results showed that the protein status of p27(Kip1) is mainly determined by p38-MAPK, whereas the role of SKP2 is less significant in the doxoroubicin-treated A549 cells. Cumulatively, we provide evidence that the DNA damage signaling is responsible for the prolonged cell cycle arrest observed after persistent chemotherapy-induced genotoxic stress. In conclusion, precise identification of the molecular mechanisms that are activated during the chemotherapeutic cycles could potentially increase the sensitization to the therapy applied.
Keywords: SKP2; Morpholines; morfoliny; Humans; DNA-PKcs; Caffeine; p27Kip1; proteinkinasa aktivovaná DNA; doxorubicin; Antineoplastic Agents; A549 Cells; kontrolní body fáze G2 buněčného cyklu; Doxorubicin; ATM; Pyrones; p38-MAPK; Chromones; ATM protein; chromony; lidé; p38 Mitogen-Activated Protein Kinases; ATR; cell cycle arrest; proteiny asociované s kinázou S-fáze; DNA-Activated Protein Kinase; S-Phase Kinase-Associated Proteins; DNA damage response; mitogenem aktivované proteinkinasy p38; pyrony; Ataxia Telangiectasia Mutated Proteins; Cyclin-Dependent Kinase Inhibitor p27; protinádorové látky; chemotherapy; poškození DNA; DNA Damage; kofein; buňky A549; G2 Phase Cell Cycle Checkpoints; inhibitor p27 cyklin-dependentní kinasy